(untitled) (Vietnam Journal of Community Medicine, 2025)
The study was conducted on 420 primary students in Quang Ninh in 2021 to describe knowledge, attitudes, and practices of the students toward soil-transmitted helminthiasis prevention. Results showed that 40% of the students knew two types of helminths; 36.7% knew one type of helminth; 10.4% knew 3 types; and 12.9% of the students did not know any type of worm. Those students who were aware of one harmful effect of soil-transmitted helminthiasis accounted for 41.7%, 44.3% knew 2 or more harmful effects, and 14% did not know any harmful effects of soil-transmitted helminthiasis. The percentage of students with knowledge about one preventive measure, 2 or more prevenetive measures, and no preventive measures for soil-transmitted helminthiasis was 49.3%, 38.8%, and 11.9% respectively. Most of the students’ families (97.1%) had hygienic latrines, and 100% of the students were dewormed. Students’ personal hygiene practices for soil-transmitted helminthiasis included foot wearing (98.3%), not drinking unboiled water (96.7%), hand washing before eating (92.9%), hand washing after defecation (92.6%), and regular deworming (100%). There should be measures on health education and communication to enhance students’ knowledge, attitudes, and practices on prevention of helminthic diseases, also deworming routines once or twice a year for primary school students.